Are we interested?: a trend analysis of sex offender internet registries - Makin, David A. (Criminal justice studies, 2018)
Traditional research on community awareness and use of sex offender registries relies upon random digit dialing and other survey instruments. While important sources of data, these sources have limitations and attempts to improve on these measures are bound to funding limitations impeding the collection of larger samples. Analyzing internet search query data associated with interest in sex offender registries from 2006-2016, we explore regional and temporal trends associated with interest in sex offender registries. Results substantiate prior research using mail and telephone surveys, and that of other similar methodologies, showing that interest in sex offender registries display low to moderate interest, which are relatively stable overtime and declining in interest.